Determining the primary factor contributed to household carbon emission by using Structural Equation Modelling (SEM) - Sharaai, Amir Hamzah; Mohd Mokhtar, Anuar; Ng, Wen Jin; Azali, Nur Afiqah (Elsevier, 2015)
Household carbon emission (HCE) is a growing concern among develop countries such as China, United States, and United Kingdom. Numerous researches have been done in order to identify the factors contributing to increase of HCE. Among the factors are numbers of occupants, household incomes, transportation fuels, electricity and liquefy petroleum gas (LPG) consumption, and waste generated by households. Unfortunately, results from these researches are possibly inapplicable at Malaysia due to difference in type of study area and climate. Thus, the purpose of this research is to identify the primary factor contributed to HCE at a residential area in Penang with the application of Structural Equation Modeling (SEM). The independent variables involved in the research are the numbers of households, household total incomes, electricity consumptions, LPG consumptions, and transportation fuel. The samples consist of 52 households using simple random sampling. There are significant positive correlations between total household income, electricity consumption, and transportation fuel with the amount of HCE. Transportation fuel was the main contributors for HCE at the residential area (β = 1.003, C.R. = 301.315, p < 0.05)